2017
DOI: 10.1371/journal.pone.0187228
|View full text |Cite
|
Sign up to set email alerts
|

A continuous morphological approach to study the evolution of pollen in a phylogenetic context: An example with the order Myrtales

Abstract: The study of pollen morphology has historically allowed evolutionary biologists to assess phylogenetic relationships among Angiosperms, as well as to better understand the fossil record. During this process, pollen has mainly been studied by discretizing some of its main characteristics such as size, shape, and exine ornamentation. One large plant clade in which pollen has been used this way for phylogenetic inference and character mapping is the order Myrtales, composed by the small families Alzateaceae, Cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 135 publications
3
23
0
Order By: Relevance
“…The resulting tree supported the monophyly of the Lythraceae and the sister relationship between Sonneratia and Trapa (Figure 1). The evolutionary relationships of Lythraceae, Onagraceae, Myrtaceae, and Melastomataceae are consistent with previously reported results (Kriebel et al 2017).…”
supporting
confidence: 92%
“…The resulting tree supported the monophyly of the Lythraceae and the sister relationship between Sonneratia and Trapa (Figure 1). The evolutionary relationships of Lythraceae, Onagraceae, Myrtaceae, and Melastomataceae are consistent with previously reported results (Kriebel et al 2017).…”
supporting
confidence: 92%
“…Molecular and palynological data together form a powerful toolset to explore the evolutionary history ( Chung, Elisens & Skvarla, 2010 ; Xie & Li, 2012 ; Kriebel, Khabbazian & Sytsma, 2017 ) by constructing a phylomorphospace. In this approach, a projection of the phylogenetic tree is plotted into a morphospace which can lead to a better understanding of the history and direction of morphological diversification within taxa ( Sidlauskas, 2008 ; Stone, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from a phylogenetic as well as evolutionary point of views, the polarity, symmetry, aperture types and exine sculpturing are the most important pollen characters [13]. It was concluded that the latitudinal gradient including moisture and temperature is important in the evolution of size and shape of pollens due to harmomegathy [27]. The diversity of shape and size of pollen of Saraca may also carry such influence.…”
Section: Discussionmentioning
confidence: 99%